A grid of online laboratories based on the iLab shared architecture - Auer, Michael E.; Zutin, Danilo Garbi [UNESP] (My University, 2012)
Active learning or working by means of online laboratories is especially valuable for distance working or education. Users in the workplace can access remote laboratories without having to travel. This flexibility is important for teleworking, education and lifelong learning. The implementation and maintenance of online labs is expensive and partially associated with high administrative efforts. These are reasons, why sharing online lab resources via different universities worldwide is a current necessity. Therefore we started at the Carinthia University of Applied Sciences together with partners a project to establish a network of interconnected online laboratories in Europe and, in a second stage, worldwide. This network is based on MIT's iLab Shared Architecture (ISA). ISA is a software architecture that offers online laboratory developers and users a common framework for using and sharing online laboratories. © 2012 American Society for Engineering Education.